Implementation of Fuel Oil Transportation Business License Policy in Bitung City - Rumintjap, Rony Adri; Dilapanga, Abdul Rahman; Tumbel, Goinpeace (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this study is to describe, analyze and describe how the implementation of the business permit policy for the transportation of Industrial Solar Non-Subsidized Fuel Oil by business entities related to downstream oil and gas business activities in Bitung City. The research method uses a qualitative approach. Data collection techniques using interviews, documentation studies and observation. The results showed that the management of the Transporters Business License still experienced obstacles. The Bitung City Environmental Service Office does not have the authority to issue recommendations needed in the process of obtaining a Transport Business License because the authority only exists at the Ministry of Environment and is not delegated to the District / City Environmental Service Office.